Binocular cataract extraction with local anaesthetic - A. Soemarsono, A. Soemarsono (Universitas Gadjah Mada, 1981)
The results of binocular cataract extraction with local anaesthetic are presented, which are good enough and not different compared with monocular cataract operations in The Eye Hospital of Gadjah Mada University. By binocular cataract extraction the hospital stay of the patient is very short and is less expensive compared with one by one operation.Key Words: binocular cataract extraction - cataracts senilis - corpus vitreum zonulysis - glaucoma